Supervising part-time employees : a guide to better productivity - Chapman, Elwood N. (Crisp Pub. Menlo ParkUS, 1994)
Distinguishes between part-time and other contingency workers. Identifies characteristics of part-time workers; and explains how to recruit, interview and train them. Lists 10 action steps for supervisors of part-time workers.